Financial Convergence in the New EU Member States - Kalin Hristov; Rossen Rozenov (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In this paper we explore the issue of financial convergence in the new EU member states (NMS). For the purposes of our analysis the countries falling into the category NMS are Bulgaria, Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia and Slovenia, i.e. all countries that joined the EU in the last decade, except Cyprus and Malta.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: 330